"If you don't improve, what's the point?" Investigating the impact of a "flipped" online exchange in teacher education. Issue 1 (25th July 2019) - Dooly, Melinda; Sadler, Randall
Abstract: This article presents a pedagogical design for teacher education that combines flipped materials, in-class instruction, and telecollaboration (also known as virtual exchange) for foreign language teacher education. The context of this study is a course on technology and language learning for future teachers in which the flipped classroom concept was applied to technology-infused collaborative teacher training between future ESL/EFL instructors located at two partner universities (one in the USA, one in Europe). The three main teaching approaches (flipped materials, in class, and telecollaborative, or "FIT") were symbiotic in that each structure reinforced the other through reception, discussion, and reflection as a means to help the student teachers bridge the gap between theory and practice. We apply classroom ethnographic discourse analysis to data sources (face-to-face and online discussion groups, student e-portfolios) to look at uptake of ideas, conceptual understanding, and successful transfer of new knowledge, and thereby identify whether the design provides significant learning opportunities for the future teachers. Although most studies of telecollaboration in language teacher education look principally at output, this approach allows an in-depth look at the learning process as knowledge is developed collaboratively between the participants.